A Case Study on Moisture Problems and Building Defects. (27th January 2015) - Othman, Nur Liyana; Jaafar, Mastura; Harun, Wan Mariah Wan; Ibrahim, Fuziah
Abstract: Hospital buildings are one of the complicated buildings that normally associate with a moisture problem. Besides environment factor, the different operation hour, poor workmanship and improper waterproofing installation also contributes to the moisture problems. Controlling the moisture problems seem to be vital in ensuring the building functionality. This study identifies the moisture problems and it's causes for the Hospital buildings in Malaysia. Based on various records obtained, this study discusses the defects according to four major building elements that are ceiling, wall, floor and roof. This paper concludes that the identified defects have great potential to affect the hospital building function.